PERAN PAMONG BELAJAR SANGGAR KEGIATAN BELAJAR DALAM PROSES DIFUSI PROGRAM PADU DI JAWA TENGAH - Agus Wijatmoko (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2006)
This research was aimed to investigate the facilitators’ performance in defusing the program of early childhood education and the contribution of education level, concept mastery, adult instructional methodology and the perception of early childhood education program to the facilitators’ performance in defusing early childhood program. The descriptive analysis shows (1) facilitators’ performance in defusing the programs of early childhood education, (2) 68% of facilitators’ educational background is bachelor (S1), (3) the level of concept mastery and adult instructional methodology tends to be satisfactory, and (4) the level of perception is categorized good. Path analysis concludes direct effect of educational level, concept mastery and perception to facilitators’ performance. While the relations among the predictors show no effects of educational level to facilitators’ perception and educational level indicates the effect to the level of concept mastery. It also indicates that the level of concept mastery gives the effect to facilitators’ perception. This research suggests Directorate General of Non Formal Education to make efforts to strengthen the roles of facilitators’ in defusing early childhood programs through formal and nonformal education.